YOUTH CULTURE AND DEVELOPMENT IN MAURITIUS (Global Journal of Management and Business Research, 2011)
Development of any society depends largely on young people and investment in today's youth is actually an investment in the future of the nation. Properly cultured youth become responsible citizens, good parents, effective decision-makers, efficient workforce and leaders of tomorrow. This study explores the relationship between youth culture and development. The main objectives of this work are to: take stock of the youth culture in society and examine the relationship between youth culture and development. Analysis, reflection and discussions are based on both secondary data and observation of youth culture in society The principal finding shows that youth culture has much positive impact on societies that inculcate good cultural values in youth and create opportunities for them to build character, acquire knowledge and skills, and develop talent and abilities. One main recommendation based on the study would be state investment in young people should be encouraged and given high priority on governmental agenda by societies willing to ensure sustainable socio-economic development and political stability.
Keywords: Development; Youth; Youth Culture; Values and Society